2022
DOI: 10.1021/acs.joc.2c01591
|View full text |Cite
|
Sign up to set email alerts
|

Switching Over of the Chemoselectivity: I2-DMSO-Enabled α,α-Dichlorination of Functionalized Methyl Ketones

Abstract: Precise control of the chemoselectivity of the halogenation of a substrate equipped with multiple nucleophilic sites is highly demanding and challenging. Most reported chlorinations of methyl ketones show poor compatibility or even exclusive selectivity toward electron-rich arene, olefin, and alkyne residues. This is attributed to the direct or in situ employment of electrophilic Cl 2 /Cl + species. Here, we reported that, even bearing those competitive residues, methyl ketones can still undergo dichlorination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Based on the aforementioned results and literature, [22][23][24]29 a plausible mechanism for the Cu@Cu-Fe 2 O 4 -promoted oxydichloromination of arylalkynes is proposed (Scheme 3d). When the alkyne is initially activated by heating in TFE/H 2 O, the chlorine radical is added from the NCS to the alkyne and then afforded vinyl radical In-A.…”
Section: Reaction Design For the Synthesis Of αα-Dichloro Ketonesmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the aforementioned results and literature, [22][23][24]29 a plausible mechanism for the Cu@Cu-Fe 2 O 4 -promoted oxydichloromination of arylalkynes is proposed (Scheme 3d). When the alkyne is initially activated by heating in TFE/H 2 O, the chlorine radical is added from the NCS to the alkyne and then afforded vinyl radical In-A.…”
Section: Reaction Design For the Synthesis Of αα-Dichloro Ketonesmentioning
confidence: 99%
“…Consequently, there has been a concerted effort to develop new synthetic methods by using α,α ‐dihaloketones as starting material in recent decades. Furthermore, traditional transformations such as oxidation, reduction, and C‐C bond formation, and innovative methods such as photocatalytic or electrocatalytic reactions have been explored 15–31 . For example, Madabhushi reported that the a,a ‐dichloro arylketones were obtained through the oxidation of terminal alkyne, respectively (Scheme a) 32,33 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the sterically inhibited 2-substituted α-tetralone skeleton has been reported to be unreactive in some palladium-catalyzed aromatization, 10 c and the electron-donating E-ring residue and its electrophilic benzyl site are also risky for single-electron oxidation. 12,14 On the basis of our research spotlight on lignan synthesis 15 as well as our long-standing interest in the I 2 –DMSO reaction system, 16 we speculated that it might be possible to take advantage of the special structural characteristics of podophyllotoxone to develop an I 2 –DMSO catalytic manifold that would fulfil our synthetic requirements. The working hypothesis is outlined in Scheme 1b.…”
mentioning
confidence: 99%